People's security survey in Brazil, Argentina and Chile: A regional comparative analysis - Lauro R. A. Ramos (Institute for Applied Economic Research (ipea), 2015)
The paper presents the main results produced by the People's Security Surveys applied in Argentina, Brazil and Chile in 2001. A comparative analysis across countries is developed, trying to point out the similarities and contrasts among behavioral patterns according to the notions of socio-economic security. A common trace for the three countries is a clear partition on the labor market and employment notions of security: those that were either unemployed or inactive at the moment the surveys were conducted had a propensity for higher turnover and discouragement; those that held a job tended to experience lower job rotation and shorter spells of unemployment. On the other hand, the comparison also reveals some differences regarding labor market sense of insecurity. There is a tendency for more criticism in Argentina, both in objective grounds and, in a stronger fashion, for the aspects related to the individuals' perception. Brazilians stand in the other extreme, whereas Chileans are somewhere in the middle.
Keywords: I31; 330